경북 농촌지역 여성 독거노인과 가족동거노인의 계절별 영양소섭취 비교 - 임영지(Young Jee Lim); 최영선(Young Sun Choi) (Korean journal of community nutrition, 2007)
For the rapidly growing elderly population, the achievement and maintenance of good nutritional status is critical to health, functioning and quality of life. Elderly women living alone have been identified as a group associated with poor nutrition. The purpose of this study was to assess dietary intakes of elderly women living alone as compared to those of elderly women living with family in a rural area and to examine seasonal variation. The subjects are 49 elderly women living alone and 41 elderly women living with family who reside in Goryeong-gun, Gyeongbuk, and their food intakes were assessed once each time in summer 2005, winter 2005-2006, and spring 2006. The average ages were 74.7 years for living alone and 72.8 years for living with family. Education level was not different between the two groups. Height, weight, body mass index, systolic and diastolic blood pressures, and fasting blood glucose were not significantly different between the two groups. Average intakes of major nutrients, nutrient adequacy ratio, mean adequacy ratio and index of nutritional quality were lower in the elderly women living alone compared with the elderly women living with family in summer, but the differences in intakes of most nutrients became insignificant both in winter and in spring. High carbohydrate and low fat diet was prevalent and intakes of carbohydrate and fat in summer deviated from macronutrient acceptable distribution ranges. Percentages of the subjects who consumed energy less than 75% of the estimated energy requirement and nutrients less than the estimated average requirement were higher than those reported by the Third National Health and Nutrition Examination Survey. In summer, the percentage of the subjects who consumed energy less than both 75% of the estimated energy requirement and 4 nutrients less than estimated average requirements was 58.5% of the elderly women living alone, which was higher than 26.5% of the elderly women living with family and that of National Nutrition Survey. Therefore, nutrition policies including nutrition education and support are necessary to improve nutritional status of elderly, especially elderly women living alone and should reflect regional and seasonal characteristics.